Marocco Stuardi, Donatella. Alcuino di York nella tradizione degli <specula principis>. Milano: Franco Angeli, 1999, 135 pp. - Hubeñak, Florencio (2002)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina; Argentina